Potential of mushroom technology as a social enterprise - The way forward - Pandey, Meera; Kumaran, G Senthil (Mushroom Research, 2021)
Mushroom cultivation began in India in 1952. Since then this industry has been oscillating between the myths of earning millions overnight and the ground realities of growing a non-conventional crop. The concept, which branched off as a lesser-known shoot of mycology, has taken unusually long to establish itself in India. Although mushroom science has the inherent subjective capability of a great impact on nutrition, agricultural waste management and environment cleansing; yet has been immensely underexploited in India. Social entrepreneurship is a novel movement gaining momentum around the world. It is a novel concept of modern business model which can find sustainable solutions to social, economic and environmental issues. It is a concept which believes in engaging in profitable commercial activities for mutual social and community gain. It works on the principle â€œTogether wewinâ€, hence community takes precedence over individuals. Social enterprises have a strong character of creating jobs and making a socially just and inclusive business model. This is the ultimate objectiveof any scientific organization or scientific technology more so of public institutions like ICAR. Mushroom technology can be a very successful social enterprise in the Indian context where agricultural crop residues to the tune of 98 million tons/annum is burnt, where millions of youth are unemployed, where there is rampant undernourishment and ever increasing threat of climate change. A majority (53%) of social enterprises in India are focussed on skill development, followed by 30% on education, 28% in agriculture-related activities, 26% in financial and clean energy,22% in healthcare, 17% on farm livelihood, 16% food & nutrition and 14% sanitation & water.There is a need to initiate mushroom technology based social enterprise which can reduce air pollution by using crop residues to grow mushrooms rather than burn, can create employment in rural unskilled sector, can help in enhancing nutrition, bring diversity to food plate and empower women. Although sporadic examples are available in India, there is a need to increase the number of such enterprises, integrate it with government programs and develop a model in partnership with public institutions who are the technology generators.